Detection of the Optical Counterpart of the Transient ULX NGC 300 ULX-1: A Nascent Black Hole-neutron Star Binary? - André-Nicolas Chené; Georgios Vasilopoulos; Lidia M. Oskinova; Clara Martínez-Vázquez (The Astrophysical Journal)
The endpoints of massive star evolution are poorly known, especially those in interacting binary systems containing compact objects, such as neutron stars or black holes (BHs). Such systems are bright in X-rays, and the most luminous among them are called ultra-luminous X-ray sources (ULXs). In this paper, we address the enigmatic NGC 300 ULX-1. Its X-ray activity started in 2010 with the supernova impostor-like event SN 2010da. In the following few years, the ULX was powered by persistent super-Eddington accretion but then it dimmed in X-rays. We present the most recent X-ray and optical observations. The Chandra and Swift telescopes confirm that SN 2010da/NGC 300 ULX-1 is not accreting at the super-Eddington level anymore. We attribute this switch in accretion regime to the donor star variability and its fast evolution. In order to gain a better understanding of the donor star’s nature, we consider its optical light curve on a decade-long timescale and show that the optical counterpart of SN 2010da/NGC 300 ULX-1 dimmed significantly over recent years. The most recent detection in the optical by the Gemini telescope reveals that the source is now >2.5 mag fainter in the ${r}^{{′} }$ band compared to the epoch when it was spectroscopically classified as a red supergiant. We discuss the nature of the abrupt changes in the donor star properties and consider, among other possibilities, the silent collapse of the donor star into a BH.